PENETAPAN KADAR VITAMIN C DAN FORMULASI SEDIAAN GRANUL INSTAN EKSTRAK KULIT JERUK KEPROK (Citrus reticulate Blanco.) - Framesti Frisma Sriarumtias; Raden Aldizal Mahendra Rizkio Syamsudin (Jurnal Penelitian Farmasi & Herbal, 2023)
Tangerines (Citrus reticulata Blanco.) is one of the national superior types of oranges that contain lots of vitamin C. Vitamin C is the simplest vitamin and has an important role on the human body. So far the use of arrowroot is only on the fruit, while the peel is only a waste. The purpose of this study is to utilize tangerine peels into preparations that have a use value for the community, in the form of instant granules. The method used in the extraction of tangerine peel is maceration by making granules using the wet granulation method, and determination of vitamin C levels by quantitative methods, UV-Vis spectrophotometry method. After obtaining the vitamin C levels, then formulations are made in the form of instant granules and quality evaluations are carried out. The results showed that vitamin C content was 130 mg / 1250 mg extract and the formula was made with the best formula, Formula 1.